Brazil's Experience with Payments for Environmental Services - Pagiola, Stefano; Carrascosa von Glehn, Helena; Taffarello, Denise (World Bank, Washington, DC, 2014)
Since 2006, there has been an explosion of Payments for Environmental Services (PES) projects in Brazil, as well as efforts to pass PES laws at federal, state, and municipal levels. Even in this short period, an extraordinarily rich range of experiences has developed, with examples of the application of PES at a variety of scales, ranging from microwatersheds to entire states; in a variety of contexts, from remote forest frontier areas to the periurban fringe of megacities like São Paulo; and using a variety of approaches, using direct payments by users, sales to regulated and voluntary carbon markets, government funding, and mixes of these approaches. In this paper, we provide an overview of Brazilian PES efforts to date, and attempt to extract some initial lessons.